Investigation mechanical properties and on surface roughness during WEDM machining of nano Cr2C3-MoS2 hybrid metal matrix composites - Ramesh Vellaichamy; Pugazhenthi Rajagopal; A. Geetha Selvarani; Itha Veeranjaneyulu; J. Immanuel Durai Raj; E. Balaji; Mamdooh Alwetaishi; S. Baskar; Krishna Moorthy Sivalingam; P. V. Elumalai (Scientific Reports)
Abstract The study aims to identify a suitable machining parameter during Wire Cut Electrical Discharge Machining (WEDM) of duralumin reinforced with varying amounts of particulates. The nano chromium carbide (Cr2C3) at 3%, 4%, and 5% and Molybdenum diSulphide (MoS2) at 2%, 3%, and 4% are chosen as reinforcements. In WEDM, machining parameters such as Pulse ON time, Pulse OFF time, and Wire Feed rate were considered, while surface roughness was measured as the response parameter. The Taguchi method of experimental design was employed to optimize the process parameters. To investigate the impact of process parameters on the surface roughness of Duralumin/Cr2C3/MoS2 composites, an analysis of variance (ANOVA) table and regression equation were constructed. The findings indicated that the weight% of Cr2C3 had the most significant influence on the machining of hybrid metal matrix composites. The optimal combination for achieving better surface roughness was determined to be 3% of Cr2C3, 2% of MoS2 a Pulse ON time of 100 µs, a Pulse OFF time of 100 µs, and a Wire Feed rate of 65 mm/sec, as determined by experimental values.